Answer:
f⁻¹(x) = (8-x)/3 and it is a Function.
Step-by-step explanation:
Given is f(x) = -3x+8
Suppose y = f(x), then y = -3x + 8
Solving for x:-
-3x + 8 = y
-3x = y - 8
3x = 8 - y
x = (8-y)/3
Now interchanging x and y:-
y = (8-x)/3
Here, y is inverse function i.e. f⁻¹(x)
Hence, f⁻¹(x) = (8-x)/3
Since f⁻¹(x) is a linear expression of x, therefore it is a function.
2x^3-8x^2-24x=2x(ax+b)(cx+d)
a=1 and d=-6
Answer:
b = 2, c = 1
Step-by-step explanation:
2x³ - 8x² - 24x == 2x(ax + b)(cx + d)
2x³ - 8x² - 24x = 2x(x² - 4x - 12)
= 2x(x + 2)(x - 6)
Answer:
Step-by-step explanation:
b=2, c=1
Answer:
the least common denominator is 40
Step-by-step explanation:
brainliest pls
Answer:
40
Step-by-step explanation:
because the the LCD of them is 40
Find x: 3x − 14 + 6 − 4 − 2x = 12
The required value of the x in the given algebraic expression is 10.
To find the value of x in the given equation, you need to solve for x. Let's simplify the equation step by step:
3x - 14 + 6 - 4 - 2x = 12
Combine like terms:
(3x - 2x) + (6 - 4) = 12
x + 2 = 12
Now, isolate x by subtracting 2 from both sides:
x = 12 - 2
x = 10
So, the value of x is 10.
Learn more about expression here:
#SPJ3
Answer:
x= 24
Step-by-step explanation:
Solve for x by simplifying both sides of the equation and then isolating the variable.
Hope this helps.
08